Treatment of acute myeloid leukemia cells in vitro with a monoclonal antibody recognizing a myeloid differentiation antigen allows normal progenitor cells to be expressed. - Bernstein, I D (1987)
Monoclonal antibody L4F3 reacts with most acute myeloid leukemia (AML) cells and virtually all normal granulocyte/monocyte colony-forming cells (CFU-GM). Our objective was to determine whether lysis of AML cells with L4F3 and complement allowed expression of normal myeloid progenitors. The five glucose-6-phosphate dehydrogenase (G6PD) heterozygous patients with AML studied manifested only a single G6PD type in blast cells and in most or all granulocyte colony-forming cells, indicating that the leukemias developed clonally. The cells remaining after L4F3 treatment from two of the patients gave rise to granulocytic colonies that expressed the G6PD type not seen in the leukemic clone, indicating that they were derived from normal progenitors (CFU-GM). L4F3-treated cells from these two patients cultured over an irradiated adherent cell layer from normal long-term marrow cultures also gave rise to CFU-GM, which were shown by G6PD analysis to be predominantly nonleukemic. In the other three patients, the progenitor cells remaining after L4F3 treatment were derived mainly from the leukemic clone. The data suggest that in vitro cytolytic treatment with L4F3 of cells from certain patients with AML can enable normal, presumably highly immature progenitors to be expressed.